PENGARUH VARIABEL EKONOMI MAKRO TERHADAP PENGANGGURAN TERDIDIKDI JAWA TIMUR TAHUN 2010-2014 - Nur Ravika Famala Sari (Jurnal Ekonomi Pembangunan, 2016)
This study aims to determine the effect of Gross Regional Domestic Product, minimum wages district or city, investment, and government expenditure resources to the educated unemployment in East Java. This study uses secondary data for 5 years from 2010-2014. The method of data analysis used in this study is Ordinary Least Square (OLS). The data used in this study is data panel which combines time series and cross section. The results of this study show that partially variables of Gross Regional Domestic Product, minimum wages district or city, domestic investment, and government expenditure significant effect on Educated Unemployment in East Java, while foreign investment no significant effect on Educated Unemployment in East Java. Amount to 70,75% of the variation of independent variables in this study may explain the variable of educated unemployment in East Java, while the remaining 29,25% is influenced by other factor outside the model estimation.